Involuntary treatment of psychiatric inpatients certified under the Saskatchewan Mental Health Services Act in a secure forensic psychiatric treatment center. (April 2015) - Adelugba, Olajide; Mela, Mansfield; Haq, Inam
A psychiatric patient prisoner is certified and treated involuntarily under the Saskatchewan Mental Health Services Act at the Regional Psychiatric Center if he/she is mentally ill, incapable of making treatment decision and is likely to cause harm to self or others. This retrospective study examined the treatment of certified patients during a 12-year period (1996 to 2007). A total of 112 patients were treated using 263 certifications during 163 separate hospital admissions. Fifty of all the certified patients (44.6%) required more than one certification, and out of these, 72% required another certification within three months of the first certification. Among those certified, schizophrenia and related psychosis (65.2%, n = 73), substance use disorder (50%, n = 56) and antisocial personality disorder (58%, n = 65) were the most common discharge diagnoses and antipsychotics, the most frequent discharge medications. Global Assessment of Functioning score of patients improved significantly ( p < .05) from 43.6 at admission to 50.4 at discharge. This functional improvement may suggest a beneficial use of certification by keeping patients in treatment. This benefit may be enhanced if the statutory duration of certification can be increased to account for the length of time required for the adequate resolution of symptoms and to reduce the need for repeat certification.